Amorphous FeF3/C nanocomposite cathode derived from metal–organic frameworks for sodium ion batteries. Issue 39 (3rd May 2017) - Zhang, Liguo; Ji, Shaomin; Yu, Litao; Xu, Xijun; Liu, Jun
Abstract : A cathode of FeF3 /C nanocomposites has been fabricated by a simple vapor-solid fluoridation route which shows superior Na-ion storage performance. Abstract : Amorphous FeF3 /C nanocomposites, where FeF3 nanoparticles are intimately anchored into a highly-graphitized porous branch-like carbon framework, have been successfully designed and fabricated from the carbonized Fe–MOFs by a novel vapor-solid fluoridation reaction and dehydration reaction. Compared to the FeF3 /C nanocomposites obtained from the precursors at various carbonization conditions, the one carried out at 700 °C for 3 h exhibits the most outstanding comprehensive sodium ion storage performance. It can deliver 302, 146, 73 mA h g −1 discharge capacities at current densities of 15, 150, 1500 mA g −1, respectively, exhibiting an excellent sodium ion capacity and rate performance. Moreover, it displays a good cycling performance with a discharge capacity of 126.7 mA h g −1 at 75 mA g −1 after 100 cycles. The outstanding electrochemical features of the FeF3 /C nanocomposites could be attributed to its amorphous structure and highly-graphited porous carbon framework, which is beneficial to the ionic and electronic transport and the reaction kinetics of electrode materials.